k-approximating circuits - Cadoli, M.; Donini, F.M.; Liberatore, P.; Schaerf, M. (IEEE transactions on computers, 2006)
In this paper, we define and study the k-approximating circuits. A circuit accepting a given set of inputs A is k-approximated by accepting inputs that lifter from one of A by at most k bits. We show that the existence of polynomial-size k-approximating circuits depends on the relation between k and the number of inputs.